Bleach Plant Effluents from the Pulp and Paper Industry - Bajpai, Pratima (SpringerBriefs in Applied Sciences and Technology, 2013)
This book covers bleach plant effluents- the most polluting effluent from the pulp and paper industry. Some of the consequences of the disposal of bleach effluents into surface waters include- disappearance of benthic invertebrates, a high incidence of fish diseases, and mutagenic effects on the aquatic fauna. This book describes the environmental impact of bleach plant effluents, environmental regulations, and measures to reduce the pollution load by internal process modification and external treatments.